Adult intussusception caused by small bowel lipoma: A case study (Indian Journal of Case Reports, 2018)
Intussusception in the adult population is an uncommon condition that can present with nonspecific signs and symptoms, both acute and chronic. We present a case of small bowel intussusception due to an underlying submucosal lipoma in an otherwise well 64-year-old lady who presented to the emergency department with a 5-day history of central abdominal pain, nausea, and vomiting with decreasing bowel motions and flatus over the past 2 days. Computed tomography suggested a small bowel obstruction secondary to an intussusception and a small bowel resection was performed. The histopathology revealed a benign submucosal lipoma of the small bowel as a lead point for a small bowel intussusception. Small bowel intussusception is not often considered in the context of a patient presenting with abdominal pain. Its treatment in the adult population, as opposed to the pediatric population, is surgical resection as it is important to exclude an underlying malignancy.